Magnitude of premenstrual dysphoric disorder and its correlation with academic performance among female medical and health science students at University of Gondar, Ethiopia, 2019: a cross-sectional study. Issue 7 (29th July 2020) - Minichil, Woredaw; Eskindir, Eleni; Demilew, Demeke; Mirkena, Yohannes
Abstract : Objective: To assess the magnitude of premenstrual dysphoric disorder (PMDD) and associated factors among female students of the College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia, 2019. Design: Institution-based cross-sectional study design. Setting: College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia. Participants: 386 participants were recruited for self-administered interview using the stratified followed by simple random sampling technique. Measurement: Data were collected by self-administered interview. Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) was used to measure PMDD. The Perceived Stress Scale (PSS) and the Oslo-3 social support are used to assess the factors. The data were checked, cleaned and entered into EpiData V.3.1 and exported to Statistical Package for Social Science (SPSS) V.21.0 for analysis. Bivariate and multivariable binary logistic regressions were used. OR with 95% CI was employed to see the strength of associations between dependent and independent variables. Variables with a p value <0.05 in multivariable logistic regression were declared as significantly associated. Result: 386 participants were involved in the study, with a response rate of 84.6%. The overall magnitude of PMDD in this study was 34.7% (30.3 to 39.1). Severe menstrual pain (adjusted OR (AOR)=2.82, 95% CI: 1.83 to 4.23), perception of an impact on academic performance due to menstrual pain (AOR=2.31, 95% CI: 1.23 to 4.32), and high perceived stress (AOR=3.52, 95% CI: 2.58 to 5.60) were significantly associated with PMDD disorder among female medical and health sciences students. Conclusion: PMDD is high among female medical and health sciences students. Thus, it needs early screening and intervention especially for those who have severe menstrual pain, perceived to have an impact on academic performance and high perceived stress.